The role of context in shaping HIV testing and prevention engagement among urban refugee and displaced adolescents and youth in Kampala, Uganda: findings from a qualitative study. Issue 5 (2nd March 2021) - Logie, Carmen H.; Okumu, Moses; Kibuuka Musoke, Daniel; Hakiza, Robert; Mwima, Simon; Kacholia, Vibhuti; Kyambadde, Peter; Kiera, Uwase Mimy; Mbuagbaw, Lawrence; ,
Abstract: Objective: To explore experiences, preferences and engagement with HIV testing and prevention among urban refugee and displaced adolescents and youth in Kampala, Uganda, with a focus on the role of contextual factors in shaping access and uptake. Methods: This qualitative community‐based study with urban refugee and displaced youth aged 16–24 living in Kampala's informal settlements involved five focus groups (FG), including two with young women, two with young men, and one with sex workers from March to May 2019. We also conducted five in‐depth key informant interviews. We conducted thematic analysis informed by Campbell and Cornish's conceptualisation of material and symbolic contexts. Results: Refugee/displaced youth participants ( n  = 44; mean age: 20.25, SD: 2.19; men: n  = 17; women: n  = 27) were from the Democratic Republic of Congo ( n  = 29), Rwanda ( n  = 11), Burundi ( n  = 3) and Sudan ( n  = 1). Participant narratives reflected material and symbolic contexts that shaped HIV testing awareness, preferences and uptake. Material contextual factors that presented barriers to HIV testing and prevention engagement included transportation costs to clinics, overcrowded living conditions that limited access to private spaces, low literacy and language barriers. Symbolic contexts that constrained HIV testing engagement included medical mistrust of HIV testing and inequitable gender norms. Religion emerged as an opportunity to connect with refugee communities and to address conservative religious positions on HIV and sexual health. Conclusion: Efforts to increase access and uptake along the HIV testing and prevention cascade can meaningfully engage urban refugee and displaced youth to develop culturally and contextually relevant services to optimise HIV and sexual health outcomes.